Sintomatologia depressiva, atitude e práticas de autocuidado de pessoas idosas com diabetes mellitus - Frazão, Maria Cristina Lins Oliveira (2021)
Introduction: Diabetes mellitus is a severe clinical syndrome that develops through a heterogeneous metabolic disorder, characterized by hyperglycemia resulting from the unsatisfactory action of insulin. The manifestations of this pathology interfere with the physical, psychological and emotional capacity of elderly people, requiring adaptation to a new lifestyle to prevent complications, which can lead to the emergence of depressive symptoms, which can negatively influence attitude and self-care. Objective: to assess depressive symptoms, attitude and self-care in elderly people with diabetes mellitus. Method: exploratory, descriptive and cross-sectional study, with a quantitative approach, carried out with 142 elderly people with diabetes mellitus in Family Health Units in the city of João Pessoa, Paraíba, Brazil. Data collection took place between the months of June and October 2019, using a semi-structured instrument to obtain data on the sociodemographic profile and health conditions, the Geriatric Depression Scale 15 items, the Questionnaire on Psychological Attitudes of Diabetes and the Diabetes Self-Care Activities Questionnaire. Data analysis was performed using descriptive and inferential statistics. The project was approved under opinion number 3,475,284. Results: 24.3% had depressive symptoms, being significantly associated with the source of income (p = 0.044), dyslipidemia (p = 0.038), complications of diabetes mellitus (p = 0.045) and retinopathy (p = 0.033). As for attitude, 93.8% had negative coping attitudes. In relation to self-care, there was a greater adherence to activities taking insulin injections as recommended (6.74), taking diabetes medications as recommended (6.55), taking the indicated number of diabetes pills (6, 52) and follow a healthy diet (5.09). The activities that showed the least adherence were eating sweets (6.01), assessing blood sugar the recommended number of times (2.86) and performing specific physical activities (1.53). In the correlation between the scales, a negative and inversely proportional correlation was observed between depressive symptoms and physical activity (p = 0.010) and foot care (p = 0.006), and an inversely proportional negative correlation between attitude and foot care (p = 0.009). Conclusions: self-care in elderly people with diabetes mellitus is influenced by the presence of depressive symptoms and a negative coping attitude. This research provides evidence that can support multidisciplinary health care for elderly people with diabetes mellitus, especially for nurses who provide continuous and comprehensive care.